Solvent-Free Protocol for Stereo Selective Crossed Aldol Condensation Assisted by Solid Acid Catalyst - S. Bhupathi, Raja; Rama Devi, B.; Dubey, P.K. (Asian Journal of Chemistry, 2011)
A highly efficient, inexpensive, recyclable, green and solvent free protocol has been developed for crossed-aldol reaction. SiO2-OSO3H has been found to be an efficient catalyst for the synthesis of 4-hydroxy-3-(3-phenyl-acryloyl)-1H-quinoline-2-one derivatives 3(a-i) from 4-hydroxy-3- acetyl-1H-quinoline-2-one (1) and substituted benzaldehydes 2(a-i). Reactions occurred smoothly with variations of the substituents. The reagent can be reused for five cycles with out sacrificing the yields and activity. This method is simple, convenient and the target compounds are produced in good to excellent yields. Compound 1 can be synthesized by the acylation of methyl anthranilate (4) with acetoacetic ester (5) in refluxing xylene and subsequent Dieckman cyclization of the intermediary 2-methoxycarbonyl anilide (6).